PEMBERDAYAAN PEMUDA DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA DI ERA PANDEMI COVID-19 DI DESA AIK BUAL - Muhammad Masruron; Ismayadi Ismayadi; Ahmad Muzayyin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2021)
This study aims to determine the response of the people of Aik Bual Village, Ramus Hamlet to the readiness to implement education during the Covid-19 Pandemic. The ultimate goal of this research is planning and development in an effort to empower the community so that sustainable development can be achieved. The implementation of this approach is to create programs and provide assistance to the people of Aik Bual Village, especially Ramus Hamlet. the methodology used is a qualitative research with a Participatory Action Research (PAR) approach. The Covid-19 Pandemic event and the Education Moratorium Policy were responded to by the Aik Bual Village community by establishing a Qur'an Education Park (TPQ) in Ramus Hamlet with the First, Diniyah, Second Fiqh Study and Third, the Establishment of a Reading Garden.